Barriers to and enablers of sustainable practices: insights from ethnic minority migrants. Issue 5 (4th May 2021) - Head, Lesley; Klocker, Natascha; Dun, Olivia; Waitt, Gordon; Goodall, Heather; Aguirre-Bielschowsky, Ikerne; Gopal, Ananth; Kerr, Sophie-May; Nowroozipour, Fatemeh; Spaven, Tess; Toole, Stephanie
ABSTRACT: Migration from the Global South to Global North is a major feature of contemporary population movements, and provides a lived experiment of the implications of moving from less resource-intensive modes of living towards more resource-intensive ones. Pre-migration practices come together in complex ways post-migration with established norms and infrastructures in destination countries. Here we examine the barriers to and enablers of sustainable practices, synthesising in-depth research from nine different studies in south-eastern Australia in relation to household water use, food growing and transport. The total sample includes 323 migrants from 33 countries. The main barriers include infrastructure and broader patterns of work and society. The main enablers are cultural norms of frugality and preferences for public transport. Barriers and enablers interact in diverse ways. We show that migrants are important contributors to inadvertent sustainabilities, but their contributions may be weakened by infrastructural, structural and cultural barriers. Addressing the diverse capacities of migrants would enhance system change for everyone.